Process modelling and simulation of crude palm oil refining - Abdul Aziz, Mustafa Kamal; Sulong, Mohd.; Morad, Noor Azian; Ibrahim, Mohd. Radzi; Sharaai, Md. Jefri (1989)
The aim of the paper is to discuss the development of a microcomputer Process modelling simulation and flowsheeting Program for Palm Oil Distillation processes i.e. Palm Oil Refining and Fatty Acids Fractionation. The scope of this work encompasses the developments of the Properties Estimation, Short-cut Design, Rigourous Design and Flowsheet modules using a microcomputer spreadsheet program. Chemical and physical properties of palm oil and derivatives were derived from 2 sources; literature and experiments. These data were input into a database-spreadsheet template to generate correlation and graphs. The Short-cut methods employ were the McCabe-Thiele Pseudo-Binary and Fenske methods to calculate number of trays. The Rigourous methods compare 3 methods; Lewis-Matheson, Thiele-Geddes and Tridiagonal-Matrix. Of which the Tridiagonal Matrix method was selected for further development. The Flowsheet method employs a dual level system by which the above Unit Operations modules are linked to a matrix of the linearised simultaneous equations representing the process flowsheet. The initial results of this system were then compared with current distillation operating conditions and distillation techniques. It showed accuracy in simulating distillation processes and highlighted the influence of trace components on the vapor-liquid equilibrium of Fatty acids and Palm Oil. The techniques were also used to investigate the viability of alternatives distillation configurations in Palm Oil processes.